1 Thessalonians 4.13–18 in Rabbinic Perspective - Moss, Candida R. (New Testament studies, 2012)
1 Thessalonians 4.16–17 has occasioned much scholarly speculation regarding Paul's conception of the resurrected body, the character of those caught up in Christ, the ultimate fate of those who are caught up in the air, and Pauline eschatology in general. The interpretation of the passage may be illuminated by comparison with rabbinic traditions in which the righteous escape judgment and destruction in Sheol by flying and being borne aloft by clouds, traditions that, given Paul's Jewish heritage, could well stand in the background of 1 Thess 4.16–17.